Treatment and Outcomes of Infections Caused by Diverse Carbapenemase-Producing Carbapenem-Resistant Enterobacterales - Lim, Fang Kang; Liew, Yi Xin; Cai, Yiying; Lee, Winnie; Teo, Jocelyn Q. M.; Lay, Wei Qi; Chung, Jasmine; Kwa, Andrea L. H. (Frontiers in Cellular and Infection Microbiology, 2020)
Background. Diverse sequence types and various carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CP-CRE) infections, which complicate treatment strategies, have emerged in Singapore. We aim to describe these CP-CRE infections and clinical outcomes according to their carbapenemase types, and determine the hierarchy of predictors for mortality that are translatable to clinical practice. Methods. Clinically significant CP-CRE infections were identified in Singapore General Hospital between 2013 and 2016. Retrospectively, all clinically relevant data were retrieved from electronic medical records from the hospital. Univariate analysis was performed. To further explore the relationship between the variables and mortality in different subset of patients with CP-CRE, we conducted recursive partitioning analysis on all study variables using the ‘rpart’ package in R. Results. 155 patients were included in the study. Among them, 169 unique CP-CRE were isolated. Thirty-day all cause in-hospital mortality was 35.5% (n=55). There was no difference in the severity of illness or any clinical outcomes exhibited by patients between the various carbapenemases. Root node began with patients with Acute Physical and Chronic Health Evaluation (APACHEII) score>=15 (n = 98; mortality risk = 52.0%) and < 15 (n = 57; mortality risk = 9.0%). Patients with APACHEII score>=15 are further classified based on presence (n = 27; mortality risk = 23.0%) and absence (n = 71, mortality risk = 62.0%) of bacterial eradication. Without bacterial eradication, absence (n = 54) and presence (n = 17) of active source control yielded 70.0% and 35.0% mortality risk, respectively. Without active source control, the mortality risk was higher for the patients with non-receipt of definite combination therapy (n = 36, mortality risk = 83.0%) when compared to those who received (n = 18, mortality risk = 47.0%). Overall, the classification tree has an area under receiver operating characteristic curve of 0.92, with a sensitivity of 0.87 and specificity of 0.91. Conclusion. Different mortality risks were observed with different treatment strategies. Effective source control and microbial eradication were associated with a lower mortality rate but not active empiric therapy for CP-CRE infection. When source control was impossible, definitive antibiotic combination appeared to be associated with a reduction in mortality.